PEMETAAN KESESUAIAN LAHAN UNTUK TANAMAN PANGAN DI KECAMATAN SOYO JAYA KABUPATEN MOROWALI UTARA - Andrean, Vidi Eka; Monde, Anthon; Nursalam, Nursalam (AGROTEKBIS, 2017)
This study aims to map land suitability classes for the development of food crops, especially crops Rice (Oryza sativa) in the Soyo Jaya Subdistrict, Morowali Utara District. This research is useful for information and recommendations about the suitability of land as well a basis for the development of crop cultivation Rice (Oryza sativa). This study was conducted from November to March 2016, located in the Soyo Jaya Subdistrict, Morowali Utara District.             The research method used is a survey method of conducting surveys directly in the field. Grouping of land suitability classes on each unit of land use systems based on the key criteria of land suitability for crops Rice (Oryza sativa).  The results showed that the actual land suitability classes are S3rfne (marginally suitable) with 36,123.54 hectare land area, while the potential land suitability class is S2rfne (appropriately enough) and the actual land suitability classes N1re       (not appropriate at this time) with an area 18,761.58 hectares, while the potential land suitability class is S3re. Key Words :   Land evaluation, land suitability, mapping, paddy rice, Soyo Jaya.